Performance Management in Practice: How Levers of Control and Autonomous Motivation Affect Work Role Performance - Nagari, Anake; Sirait, Afni (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This research explores how the practice of management control systems shapes employees’ motivation and performance. It evaluates an integrated model of self-determination theory, the levers of control, and the work role performance framework. Data were collected via an online survey involving 333 employees in Indonesia from diverse sectors, and the analyses relied on structural equation modeling and ANOVA. The results indicate that using belief control systems or interactive control systems on their own, as well as combining diagnostic and interactive controls, enhances autonomous motivation. Conversely, boundary control systems and diagnostic control systems, when used independently, are associated with lower autonomous motivation. Autonomous motivation, in turn, contributes positively to work role performance, which covers proficiency, adaptivity, and proactivity. The study also finds that autonomous motivation serves as a partial mediator between the use of interactive controls, joint use of diagnostic and interactive controls, and work role performance. The findings emphasize the value of thoughtfully designing management control systems to support stronger motivation and better performance outcomes, and they highlight the importance of examining work role performance as a broader indicator of effectiveness, particularly in dynamic and interdependent work settings.